2000
DOI: 10.1007/s004010000180
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1 and claudin-5 expression and tight junction morphology are altered in blood vessels of human glioblastoma multiforme

Abstract: The aim of the study was to characterize the interendothelial junctions in tumor microvessels of five cases of human glioblastoma multiforme. In addition to morphological analysis, tumors were screened for the expression of junctional proteins, such as occludin, claudin-1, ZO-1 and catenins. The expression of the tight junction protein claudin-1 was lost in the majority of tumor microvessels, whereas claudin-5 and occludin were significantly down-regulated only in hyperplastic vessels. As shown by freeze-fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
281
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(297 citation statements)
references
References 45 publications
7
281
0
1
Order By: Relevance
“…Thus, the reduced expression of claudins in cancer supported the hypothesis that tumorigenesis is associated with tight junctions disruption and that this process is critical for reduced cohesion and invasiveness as well as the limited differentiation capacity of cancer cells. Decreased expression of tight junction proteins, such as claudins, in cancer results in reduced cell adhesion during the progression of cancer to metastasis (37,38). The results of the present study indicated that claudin-1 expression was reduced in poorly-differentiated gastric adenocarcinomas compared with well-to moderately-differentiated gastric adenocarcinomas; in addition, the present findings confirmed that the loss or downregulation of tight junction proteins in cancer cells was essential for tumorigenesis.…”
Section: Claudin-1 Claudin-4 ----------------------------------------supporting
confidence: 79%
“…Thus, the reduced expression of claudins in cancer supported the hypothesis that tumorigenesis is associated with tight junctions disruption and that this process is critical for reduced cohesion and invasiveness as well as the limited differentiation capacity of cancer cells. Decreased expression of tight junction proteins, such as claudins, in cancer results in reduced cell adhesion during the progression of cancer to metastasis (37,38). The results of the present study indicated that claudin-1 expression was reduced in poorly-differentiated gastric adenocarcinomas compared with well-to moderately-differentiated gastric adenocarcinomas; in addition, the present findings confirmed that the loss or downregulation of tight junction proteins in cancer cells was essential for tumorigenesis.…”
Section: Claudin-1 Claudin-4 ----------------------------------------supporting
confidence: 79%
“…Transfection of CLN-5 into cell lines is associated with induction of barrier properties, whereas CLN-5 -/-mice show selective BBB opening and die perinatally (6). These data suggest CLN-5 as a key determinant of trans-endothelial resistance at the BBB, and its disruption has previously been linked to barrier breakdown in glioblastoma multiforme, a neoplastic disorder of human CNS (31). More recently, down-regulation of CLN-5, OCLN, and ZO-1 has also been shown to result in disruption of the blood-spinal cord barrier in SOD1 mutant models of amyotrophic lateral sclerosis (32).…”
Section: Discussionmentioning
confidence: 80%
“…While CLDN5 is highly expressed in the brain endothelium, CLDN1 expression in cerebral capillaries is low and was only confirmed to be present in human, rat, and sheep BBB 3, 30, 31. Regardless of the low expression, CLDN1 function in human brain capillaries is critical for the maintenance of the BBB integrity during neuroinflammation and brain tumor 29, 44. In the experimental model of EAE, the induced expression of CLDN1 in only 30% to 50% of brain vasculature was sufficient for BBB strengthening and significant amelioration of the disease 45.…”
Section: Discussionmentioning
confidence: 99%